(untitled) (Revista de História da UEG (REVHIST), 2019)
Abstract: The essay discusses the relevance of the studies of religion from a usual question about its scientific validity. It problematizes the kind of historical consciousness of religions forged by the secularization thesis in its teleological version as the fulcrum of perspectives that negatively represent the religious studies. In the final section of this essay, the argumentation about the relevance of the studies on religion is developed from the place of faith into the contemporary landscape. Keywords: Religion. History of religions. Modernity.